Pincer Maneuver: Legality of China’s Economic Measures towards India - Gemilang, Adinda Balqis Tegarmas (Indonesian Comparative Law Review, 2022)
China today has an enormously massive and diverse industrial sector which cemented its role as the world’s factory. This status is mainly borne from cheap, plentiful and capable workforce that given by the size of its population. Increasingly belligerent stances taken by the Chinese Communist Party (CCP) in combination with myriad of other factors have led industries to slowly move their production elsewhere. The alternative, in form of China’s nemesis, India which has started to woo manufacturer to  do business with them as a more competitive and open market in combination with the abundance of cheap and capable workforce. China in realizing this move are now exposed to the existential problem of power. With the wealth accumulated, China has started curbing the effect of the relocation of its manufacturing sectors to India. Initiatives and program that they create have strangely unaffected India in its efforts to enter into the global manufacturing and distribution system. The paper aims at answering the question on the legality of China’s economic measures toward India from the perspective of the existing international law. This normative legal research relies on primary and secondary sources. The study found that the mentioned economic measures are in line with the applicable international law.